Effects of Leukocyte- and Platelet-Rich Fibrin Alone and Combined With Hyaluronic Acid on Pain, Edema, and Trismus After Surgical Extraction of Impacted Mandibular Third Molars - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2018)
Purpose: In this prospective, randomized, double-blind controlled study, we evaluated the effects of leukocyte-and platelet-rich fibrin (L-PRF) alone and combined with a hyaluronic acid (HA) sponge on pain, edema, and trismus after mandibular third molar surgery. Patients and Methods: In total, 60 patients were included in this study. The patients were randomly divided into 3 groups: L-PRF group (L-PRF was applied to the socket), L-PRF-plus-HA group (L-PRF combined with HA was applied to the socket), and control group (nothing was applied). The primary outcome variables were edema (tragus to pogonion, tragus to labial commissure, and angulus mandibulae to lateral canthus), trismus on postoperative days 2 and 7, and postoperative pain scores on a visual analog scale from hour 6 to day 7. Results: After extraction, the tragus-to-pogonion values were significantly higher in the control group both on day 2 (higher than L-PRF-plus-HA group) and on day 7 (higher than both groups). The mean increase in tragus-to-labial commissure values on day 2 was significantly higher in the control group than in the L-PRF-plus-HA group. The mean increase in angulus mandibulae-to-lateral canthus values on days 2 and 7 was significantly higher in the control group than in the L-PRF and L-PRF-plus-HA groups. There was no significant difference among groups in trismus and visual analog scale pain scores. Analgesic intake on the day of surgery in the L-PRF-plus-HA group was significantly lower. Conclusions: Our results imply that L-PRF, particularly when combined with HA, can be used to minimize postoperative edema after mandibular third molar surgery. However, further studies with larger samples are required. (C) 2017 American Association of Oral and Maxillofacial Surgeons
Keywords: POSTOPERATIVE PAIN; GROWTH-FACTORS; PLASMA PRP; SURGERY; REGENERATION; SOCKETS; TRAMADOL; REMOVAL; REPAIR; TISSUE